Geometry - Wheater, Carolyn C. (McGraw-Hill Education, 2010)
With more than 1,000,000 copies sold, Practice Makes Perfect has established itself as a reliable practical workbook series in the language-learning category. Now, with Practice Makes Perfect: Geometry, students will enjoy the same clear, concise approach and extensive exercises to key fields they've come to expect from the series--but now within mathematics. Practice Makes Perfect: Geometry is not focused on any particular test or exam, but is complementary to most curricula. Because of this approach, the book can be used by struggling students needing extra help, readers who need to firm up skills for an exam, or those who are returning to the subject years after they first studied it. Its all-encompassing approach will appeal to both U.S. and international students.